CONTRIBUTIONS OF IMO STATE AGENCY FOR COMMUNITY AND SOCIAL DEVELOPMENT PROJECT AND SUSTAINABLE DEVELOPMENT IN ORLU LOCAL GOVERNMENT AREA, IMO STATE NIGERIA (2010 - 2020) - Duru, Kennedy Uchenna; Osita-Njoku, Agnes (African Journal of Social and Behavioural Sciences, 2024)
This research was carried out to determine the extent Imo State Agency for Community and Social Development Project (CSDP) contributes to socio-economic development in the study area. The researcher used structural functional theory as the framework of analysis. A descriptive survey was applied and data were collected through primary sources. The population of the study consisted of 350 town union representatives from 35 autonomous communities in Orlu LGA. The population was also used as the sample since the census enumeration method was used. Data analysis was done using percentages, means and Pearson Product Moment Correlation Coefficient at 0.05 level of significance with the aid of the Statistical Package for Social Sciences. The study revealed a significant relationship between the CSDP interventions and key indicators in Orlu. Specifically, there was a significant positive association between CSDP – supported school rehabilitation efforts and school enrolment rates. Additionally, a significant relationship was observed between CSDP health interventions and life expectancy. It was recommended that the CSDP should intensify efforts on schools’ rehabilitations by maintaining existing primary and secondary schools and building more classroom blocks. Furthermore, the government through CSDP should help in constructing and maintaining primary health Centres so that people in Orlu LGA will have access to affordable and quality healthcare services.